Genome-wide association study of chlamydia reinfection in African American women - Tiwari, Hemant K.; Patki, Amit; Srinivasasainagendra, Vinodh; Vejandla, Sandeep C.; Sadeesh, Archish; Gupta, Kanupriya; Appah, Mary; Geisler, William M. (Frontiers in Immunology, 2025)
BackgroundChlamydia trachomatis (Ct) is a bacterium that causes chlamydia, the most diagnosed bacterial sexually transmitted infection (STI) in the world. In the U.S., chlamydia is most prevalent among non-Hispanic African American (AA) individuals, implying substantial racial disparity. Despite prevention and control efforts, reinfection is common, suggesting that some individuals have insufficient protective immunity to Ct. To better understand the genetically mediated risks of chlamydia reinfection, we sought to identify genetic loci associated with reinfection using a Genome-Wide Association Study (GWAS) approach.MethodWe performed GWAS in 300 AA women with versus without chlamydia reinfection based on Ct testing done about 3 months after chlamydia treatment. We conducted logistic regression models to test the additive genetic effect and used Firth regression to confirm the association results. Furthermore, we performed post-GWAS analysis to determine the functional consequences of GWAS hits, including fine-mapping, expression quantitative loci (eQTL) and chromatin interaction analyses, tissue and cell-type expression, and pathway analysis.ResultsGWAS identified 17 suggestive genomic regions of interest. Five genomic regions out of 17 were identified as strongly associated with reinfection, using linkage disequilibrium and fine mapping. The positional mapping, eQTL, and chromatin interactions (CIs) analyses further identified 12 gene targets. Among the 12 gene targets, CHIT1, ADORA1, and CHI3L1 in chromosome 1 (chr. 1); TDRP, FBXO25, and SULF1 in chr. 8; and the SOCS6 gene in chr. 18, were functionally relevant to reinfection.ConclusionsThis GWAS study in AA women identified multiple novel genes associated with chlamydia reinfection, including CHIT1, CHI3L1, ADORA1, ALK, TDRP, FBXO25, LINC01592, SULF1, and SOCS6, which are involved in the immune response. CHIT1, ADORA1, CHI3L1, TDRP, FBOXO25, SULF1, and SOCS6 were identified using CI/eQTL mapping.